Optimisation of Water Distribution Networks Design by Minimizing the Total Length - LAHIOUEL, Y.; CHAOUI, K.; KHEZZAR, L.; HADDAD, A.; AZARI, Z. (Engineering Transactions, 2005)
The aim of the present work is to establish a new algorithm for the optimization of the design of water distribution networks. The proposed algorithm makes it possible to connect the nodes and the sources using the shortest path to obtain a final looped configuration. A novel method, the "minimal length algorithm", is proposed. It uses the advantages of existing methods and exceeds their limitations. Some of the well-known existing methods are the shortest path algorithm, the minimum spanning tree algorithm and a novel method published previously. The developed algorithm is implemented into a user-friendly interactive computer program which allows the design of looped systems with minimal length ensuring least cost, reliability of the network and hence the availability of water.